2019
DOI: 10.1039/c9fo00075e
|View full text |Cite|
|
Sign up to set email alerts
|

Grifola frondosapolysaccharides ameliorate lipid metabolic disorders and gut microbiota dysbiosis in high-fat diet fed rats

Abstract: G. frondosa polysaccharides have the potential to ameliorate lipid metabolic disorders in part through modulating gut microbiota and mRNA expression of genes involved in hepatic lipid and cholesterol metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(77 citation statements)
references
References 52 publications
7
70
0
Order By: Relevance
“…Lipid drops are usually accumulated in liver tissue, causing hepatic structural disruption and dysfunction, which ultimately leads to liver hypertrophy and fatty liver disease [21]. Therefore, controlling lipid accumulation in the liver can prevent the progression of lipid metabolic disorders [22]. In this study, fatty liver disease was mimicked in broilers by consecutive injection of CORT, showing with the typical characteristics of fatty liver disease as the previous report [10].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Lipid drops are usually accumulated in liver tissue, causing hepatic structural disruption and dysfunction, which ultimately leads to liver hypertrophy and fatty liver disease [21]. Therefore, controlling lipid accumulation in the liver can prevent the progression of lipid metabolic disorders [22]. In this study, fatty liver disease was mimicked in broilers by consecutive injection of CORT, showing with the typical characteristics of fatty liver disease as the previous report [10].…”
Section: Discussionsupporting
confidence: 64%
“…A study have shown that more abundance of Proteobacteria was found in fecal of children who were high-fat, and low-ber consumers [38]. Notably, Intestinimonas, a short-chain fatty acids (SCFA) -producing intestinal bacterium [22], was enriched in the CORT&PB group. It has been reported that SCFA is generally considered to have many important effects on maintaining host health such as providing nutrients and energies for the host [39], and reduced production of SCFA is a crucial pathogenic cause in fatty liver disease [40].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the same study demonstrated changes in farnesoid X receptor (FXR)-dependent gene expression, including increases in Cyp7a1, suggesting enhanced bile acid synthesis [10]. Mushroom polysaccharide supplementation of a high fat diet led to similar changes in gene expression, along with increases in Parasutterella that were correlated with reductions in serum lipids [24]. While total cholesterol levels were decreased, although not signi cantly, by the introduction of Parasutterella, LDL levels were not measured [10], suggesting that the mechanisms documented in mice could be acting similarly in humans consuming RPS, speci cally those with above-threshold levels of Parasutterella.…”
Section: Discussionmentioning
confidence: 83%
“…52 As a member of the Barnesiellaceae family, Barnesiella is also a SCFA producer. 53 It has recently been reported that multiple bioactive components, such as mannoligosaccharides (MOS) from spent coffee grounds, 54 polyphenolrich cranberry extracts, 55 Grifola frondosa polysaccharides, 56 polyunsaturated fatty acids from Spirulina platensis, 57 and decaffeinated green and black tea polyphenols, 58 might regulate glucose homeostasis, insulin sensitivity and lipid metabolism as well as modulate body weight through modifying gut microbiota, including increasing the abundance of Barnesiella. Moreover, improving T2DM with a traditional Chinese medicine, Xiexin Tang, was also associated with enriched Barnesiella.…”
Section: Discussionmentioning
confidence: 99%